Metacognitive Labeling of Contentious Claims: Facts, Opinions, and Conspiracy Theories - Brotherton, Robert; Son, Lisa K. (Frontiers in Psychology, 2021)
Congenial information is often judged to be more valid than uncongenial (but otherwise equivalent) information. The present research explores a related possibility concerning the process by which people label a claim as fundamentally factual (open to proof or disproof) or opinion (a matter of personal preference not amenable to falsification). Rather than merely being more skeptical of uncongenial claims, uncongenial claims may be metacognitively categorized as more opinion than factual, while congenial claims may be more likely to be categorized as factual. The two studies reported here attempt to trace a preliminary outline of how claims are categorized as fact, opinion, or some mix of the two in the context of mundane claims, contentious political issues, and conspiracy theories. The findings suggest that claims are more likely to be labeled factual (and, to a lesser extent, are less likely to be labeled opinion) to the extent that one subjectively agrees with the content of the claim. Conspiracy theories appear to occupy a middle-ground between fact and opinion. This metacognitive approach may help shed light on popular debate about conspiracy theories, as well as seemingly intractable political disagreements more generally, which may reflect fundamental differences in the perceived epistemic foundations of claims rather than simple disagreement over the facts of the matter. Given limitations of the stimuli and participant samples, however, it remains to be seen how generalizable these findings are.